The Relationship between Corporate Social Responsibility and Corporate Financial Performance: Evidence from China - GUO, SHUANG (2018)
1. Abstract Many countries (especially developed countries) have studied the association between corporate social responsibility (CSR) and corporate financial performance (CFP) (Ullmann, 1985; Soloman and Hansen, 1985; Cornell and Shapiro, 1987; Wang and Sarkis, 2017; Mcwilliams and Siegel 2001). But few studies about this topic have been conducted in China mainland. Actually, the situation in China mainland is unsatisfactory. The aim of many companies is to maximize the interests of shareholders, and they just pursuit profits and neglect responsibilities for other stakeholders, leading to a series of social issues, such as toxic milk powder and food poisoning. Therefore, studying the correlation between CSR and CFP in China is of great significance.